The first Antarctic whaling season of Admiralen (1905–1906): the diary of Alexander Lange - Adie, Susan; Basberg, Bjørn L; Lange, Alexander (Polar Record, 2009)
The first factory ship of the so-called modern era of Antarctic whaling was Admiralen, arriving together with two smaller catcher boats in the South Shetland Islands in January 1906, after a period of whaling in the Falkland Islands. The expedition leader was Alexander Lange, a Norwegian whaler with a long experience from whaling in northern Norway and Spitsbergen. He kept a diary for a considerable period and this covered several whaling voyages. The one dealing with the pioneer Antarctic season of 1905–1906 has been translated from Norwegian into English and is presented here with an introduction that places the expedition into its wider context.
Keywords: Nordmenn; Norge; Sørishavet; dagbøker; hvalfangere; hvalfangst; pelagisk

Isostatic stability of the East Antarctic station Dumont d’Urville from long-term geodetic observations and geophysical models - Amalvict, Martine; Willis, Pascal; Wöppelmann, Guy; Ivins, Erik R.; Bouin, Marie-Noëlle; Testut, Laurent; Hinderer, Jacques (Polar Research, 2009)
Geodetic measurements of the vertical crustal displacement collocated with absolute gravity changes provide a discriminatory measurement of present-day glacial changes, versus more deeply seated rock motions caused by glacial isostatic adjustment (GIA). At the East Antarctic station of Dumont d’Urville, we compare the displacements derived from continuous DORIS (1993.0– 2006.0) and Global Positioning System (GPS) (1999.0–2005.7) data, and observed changes in absolute gravity (2000–2006), with the predicted vertical displacement and change in gravity from GIA modelling. The geodetic results have mutual self-consistency, suggest station stability and provide upper bounds on both GIA and secular ice mass changes. The GIA models tend to predict amplitudes of rock motion larger than those observed, and we conclude that this part of Antarctica is probably experiencing a slight gain in ice mass, in contrast to West Antarctica.
Keywords: Antarktis; breendringer; geodesi; geofysikk; innlandsis; tidevannsmålinger

Revisiting sites of the South Pole Queen Maud Land Traverses in East Antarctica: Accumulation data from shallow firn cores - Anschütz, Helgard; Müller, Karsten; Isaksson, Elisabeth; McConnell, Joseph R.; Fischer, Helmut; Miller, Heinz; Albert, Mary; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2009)
[1] Ground-based accumulation measurements are scarce on the high East Antarctic plateau, but highly necessary for model validation and the interpretation of satellite data for the determination of Antarctic mass balance. Here, we present accumulation results obtained from four shallow firn cores drilled in the Antarctic summer season 2007/2008. The cores were drilled along the first leg of the Norwegian-US IPY traverse through East Antarctica, visiting sites like Plateau Station and Pole of Relative Inaccessibility that have been covered by the South Pole Queen Maud Land Traverses (SPQMLT) in the 1960s. Accumulation has been determined from volcanic chronology established from the conductivity records measured by dielectric profiling (DEP). The Tambora 1815/unknown 1809 double peak is clearly visible in the conductivity data and serves as a reliable time marker. Accumulation rates averaged over the period 1815–2007 are in the range of 16 to 32 kg m−2 a−1, somewhat lower than expected from the SPQMLT data. The spatial pattern is mainly influenced by elevation and continentality. Three of the firn cores show a decrease of more than 20% in accumulation for the time period 1815–2007 in relation to accumulation rates during the period 1641–1815. The spatial representativity of the firn cores is assessed by ground-penetrating radar, showing a rather smoothly layered pattern around the drill sites. Validation of the DEP results is utilized by comparison with chemistry data, proving the validity of the DEP method for dating firn cores. The results help understanding the status of the East Antarctic ice sheet and will be important for e.g. future model-derived estimates of the mass balance of Antarctica.
Keywords: Dronning Maud Land; geofysikk; glasiologi; innlandsis; isbreer; vulkaner

What can GPR tell us about cryoconite holes? 3D FDTD modeling, excavation and field GPR data - Brandt, Ola; Taurisano, Andrea; Giannopoulos, Antonios; Kohler, Jack (Cold Regions Science and Technology, 2009)
Cryoconite holes form on ice due to enhanced ablation around particles deposited on the surface, and are present in the ablation area of glaciers worldwide. Here we investigate the use of Ground Penetrating Radar (GPR) as a non-destructive method to monitor and map cryoconite holes. We compare GPR data obtained from the Jutulsessen blue ice area in Dronning Maud Land, Antarctica, with modeled GPR data. The modeled GPR response to cryoconite holes is numerically calculated by solving Maxwell's equations with a 3D Finite-Difference Time-Domain (FDTD) scheme. The model includes a realistic shielded bowtie antenna and dimensions and constituent parameters of cryoconite holes excavated in the field. We have performed what-if scenarios with controlled variation of single parameters. We show that GPR can be used to determine the horizontal extent, depth and whether a cryoconite hole is frozen or contains liquid water, information unavailable from visual surface inspection. The cryoconite thickness can, for completely frozen holes, be determined to within a 1/4 of the GPR center frequency wavelength. The exact water content is not readily extractable because the GPR response is influenced by many other factors such as: cryoconite thickness, shape and roughness, as well as antenna ground coupling.
Keywords: Dronning Maud Land; georadar; glasiologi

Mixing on the continental slope of the southern Weddell Sea - Daae, Kjersti L.; Fer, Ilker; Abrahamsen, E. Povl (Journal of Geophysical Research: Oceans, 2009)
Shipboard hydrography and current profiles collected in 2003 and time series from moored current meters deployed in late 1990s are analyzed to study the variability of mixing in the southeastern Weddell Sea. Profiles of eddy diffusivity Kρ are inferred from fine-scale shear (vertical derivative of horizontal velocity) and strain (vertical derivative of isopycnal displacement) variance using parameterizations which relate the internal wave energy to the dissipation rate at small scales. The highest mixing rates are seen near the bottom where the eddy diffusivities are elevated by 1 order of magnitude from those in the interior and exceed 10−4 m2 s−1. The observations show latitudinal variability in Kρ, particularly near the bottom, where Kρ significantly increases near 74° 28′S, the critical latitude for lunar semidiurnal (M2) tides. In this region, the critical latitude coincides with near-critical topography on the upper continental slope, a situation which favors generation of M2 internal waves. Consistent with the results from fine-scale shear and strain parameterizations, which indicate highest bottom diffusivities near the critical latitude, independent analysis of current time series from moored instruments shows a thickening of the frictional bottom boundary layer near the critical latitude. Semidiurnal tidal dynamics at the upper continental slope together with the critical latitude effects lead to mixing that might significantly affect the regional heat budget and the circulation in the study area.
Keywords: Sørishavet; Weddellhavet; bunnvann; geofysikk; hydrografi; kontinentalmargin; oseanografi; vannvirvler

Report from the Workshop on the Development of the Weddell Sea - Dronning Maud Land Regional Working Group SOOS - de Steur, Laura; Gutt, Julian; Moreau, Sebastien ([Zenodo], 2009)
This report summaries the first workshop of the Southern Ocean Observing System (SOOS) Weddell Sea and Dronning Maud Land (WS-DML) Regional Working Group held Tromsø, Norway, in January 2019.
Keywords: Dronning Maud Land; Sørishavet; geofysikk; geologi; konferanse; symposium

Tropical Pacific - high latitude south Atlantic teleconnections as seen in δ18O variability in Antarctic coastal ice cores - Divine, Dmitry; Isaksson, Elisabeth; Kaczmarska, Marzena; Godtliebsen, Fred; Oerter, Hans; Schlosser, Elisabeth; Johnsen, Sigfus J; van den Broeke, M; van de Wal, R S W (Journal of Geophysical Research: Atmospheres, 2009)
We use a network of eight ice cores from coastal Dronning Maud Land (DML), Antarctica, to examine the role of the tropical ENSO (El Niño-Southern Oscillation) in the temporal variability of δ18O in annual accumulation. The longest record from the S100 ice core covering the period 1737–1999 is used to analyze the teleconnections between the tropical Pacific and coastal DML on decadal scales and longer. A shorter stacked coastal DML δ18O series spanning 1955–1999 is constructed to assess the variability of ENSO teleconnection on interannual scales. Results suggest that, on typical ENSO timescales of 2–6 years, the strength of the teleconnection varies in time, being stronger for years with generally negative phase of the Southern Annular Mode (SAM). On the timescales of approximately two decades (bidecadal), positive isotope anomalies are associated with oceanic warming and a westward sea surface temperature (SST) gradient in the equatorial Pacific. Bidecadal variability in SAM, forced by the tropical Pacific, is proposed as a critical element in the teleconnection. Our analysis suggests that a multidecadal positive trend in the annual mean δ18O values from the analyzed cores can be indicative of the atmospheric warming that begun in this part of the DML already in the 1910s. The trend in δ18O, quantified in terms of long-term surface air temperature (SAT) changes, is consistent with the instrumental data. Yet, we speculate that the accurate estimation of SAT trends requires an assessment of the potential role of secular SAM and sea ice extent changes in shaping the isotopic signal.
Keywords: Dronning Maud Land; Sørishavet; geofysikk; klima

Shelf-derived iron inputs drive biological productivity in the southern Drake Passage - Dulaiova, H.; Ardelan, M. V.; Henderson, P. B.; Charette, M. A. (Global Biogeochemical Cycles, 2009)
In the Southern Ocean near the Antarctic Peninsula, Antarctic Circumpolar Current (ACC) fronts interact with shelf waters facilitating lateral transport of shelf-derived components such as iron into high-nutrient offshore regions. To trace these shelf-derived components and estimate lateral mixing rates of shelf water, we used naturally occurring radium isotopes. Short-lived radium isotopes were used to quantify the rates of shelf water entrainment while Fe/228Ra ratios were used to calculate the Fe flux. In the summer of 2006 we found rapid mixing and significant lateral iron export, namely, a dissolved iron flux of 1.1 × 105 mol d−1 and total acid leachable iron flux of 1.1 × 106 mol d−1 all of which is transported in the mixed layer from the shelf region offshore. This dissolved iron flux is significant, especially considering that the bloom observed in the offshore region (0.5–2 mg chl a m−3) had an iron demand of 1.1 to 4 × 105 mol Fe. Net vertical export fluxes of particulate Fe derived from 234Th/238U disequilibrium and Fe/234Th ratios accounted for only about 25% of the dissolved iron flux. On the other hand, vertical upward mixing of iron rich deeper waters provided only 7% of the lateral dissolved iron flux. We found that similarly to other studies in iron-fertilized regions of the Southern Ocean, lateral fluxes overwhelm vertical inputs and vertical export from the water column and support significant phytoplankton blooms in the offshore regions of the Drake Passage.
Keywords: Sørishavet; Sørishavsstrømmen; biogeokjemi; fytoplankton; marin kjemi; oseanografi; radiumisotoper

Fluid infiltration, heat transport, and healing of microcracks in the damage zone of magmatic veins: Numerical modeling - Engvik, Lars; Stöckhert, Bernhard; Engvik, Ane K (Journal of Geophysical Research: Solid Earth, 2009)
Alteration halos with sharp boundaries are flanking pegmatitic veins in high-grade metamorphic and magmatic rocks of Dronning Maud Land, Antarctica. These halos are interpreted to represent the damage zone, formed as the wake of the process zone at the tip of the propagating magma-filled fracture and infiltrated by the fluid phase liberated from the crystallizing hydrous melt. On the basis of a set of assumptions, our numerical model explores the time scales of the infiltration processes, taking into account the combined effects of fluid flow, heat transfer, and temperature-dependent decay of interconnected porosity due to microcrack healing. Assuming an initial magma temperature of 700°C, a far field temperature in the host rock of 300°C, an initial porosity range of 0.5–2% in the damage zone, a permeability of 10−16 m2, and a pressure difference of 300 MPa, we find that the fluid infiltration into the damage zone proceeds within seconds to minutes and that the fluid flow contributes significantly to the heat transfer into the host rock. Assuming an initial microcrack aperture of 1 μm, the model predicts that the crack healing time scale is significantly longer than that of fluid infiltration in the case of thin veins with narrow damage zones; in this case, crack healing does not hinder fluid infiltration. Only for thick veins with high heat content and prolonged crystallization history does permeability become reduced by crack healing during progressive fluid infiltration. The results indicate that the formation of the alteration halos flanking pegmatitic veins may be a quasi-instantaneous process on geological time scales.
Keywords: Dronning Maud Land; geofysikk; geologi; mineralogi

Tracing biomass burning aerosol from South America to Troll Research Station, Antarctica - Fiebig, Markus; Lunder, Chris René; Stohl, Andreas (Geophysical Research Letters, 2009)
The atmospheric observatory at the Norwegian Research Station Troll in Queen Maud Land, Antarctica, holds, since February 2007, the first all-year Antarctic atmospheric aerosol particle number size distribution measurements. These are colocated with measurements of the aerosol absorption and spectral scattering coefficients. In June 2007, this instrument set observed an aerosol whose properties were indicative of a biomass burning aerosol. These properties included two log-normal size distribution modes with median particle diameters of 0.105 μm and 0.36 μm, sharply falling off to smaller and larger sizes, and peaks in scattering and absorption coefficient. With backward plume calculations of the Lagrangian transport model FLEXPART and the MODIS fire activity product, a source-receptor relationship was established between biomass burning events in Central Brazil and the aerosol seen at Troll. This is the first direct evidence that the Antarctic continent is susceptible to emissions from as far north as Southern tropical latitudes.
Keywords: Dronning Maud Land; Troll forskningsstasjon; biomasse; klimatologi; meteorologi; utslipp

Evidence for northward expansion of Antarctic Bottom Water mass in the Southern Ocean during the last glacial inception - Govin, Aline; Michel, Elisabeth; Labeyrie, Laurent; Waelbroeck, Claire; Dewilde, Fabien; Jansen, Eystein (Paleoceanography, 2009)
We investigated deep water changes in the Southern Ocean during the last glacial inception, in relationship to surface hydrology and global climatology, to better understand the mechanisms of the establishment of a glacial ocean circulation. Changes in benthic foraminiferal δ13C from three high-resolution cores are compared and indicate decoupled intermediate and deep water changes in the Southern Ocean. From the comparison with records from the North Atlantic, South Atlantic, and the Southern Ocean, we show that the early southern deep water δ13C drop observed at the MIS 5.5–5.4 transition occurred before any significant reduction of North Atlantic Deep Water ventilation. We propose that this drop is linked to the northward expansion of poorly ventilated Antarctic Bottom Water (AABW) mass in the Southern Ocean. Associated with an early cooling in the high southern latitudes, the westerly winds and surface oceanic fronts would migrate equatorward, thus weakening the upwelling of Circumpolar Deep Waters. Reduced heat brought to Antarctic surface waters would enhance sea ice formation during winters and the deep convection of cold and poorly ventilated AABW.
Keywords: AABW; Sørishavet; bunnvann; havstrømmer; hydrologi; paleoklimatologi; paleoseanografi; vannmasser

Survey of waste water disposal practices at Antarctic research stations - Gröndahl, Fredrik; Sidenmark, Johan; Thomsen, Ann (Polar Research, 2009)
To inform the future practices to be employed for handling waste water and grey water at the Swedish Antarctic station,Wasa, in Dronning Maud Land, the Swedish Polar Research Secretariat took the initiative to survey the practices of the 28 nations with stations in Antarctica. A questionnaire was sent out to all members of the Antarctic Environment Officers Network during the autumn of 2005. Questions were asked about the handling of waste water and grey water, the type of sewage treatment, and installation and operational costs. The response to the questionnaire was very good (79%), and the results showed that 37% of the permanent stations and 69% of the summer stations lack any form of treatment facility. When waste water and grey water containing microorganisms are released, these microorganisms can remain viable in lowtemperature Antarctic conditions for prolonged periods. Microorganisms may also have the potential to infect and cause disease, or become part of the gut flora of local bird and mammal populations, and fish and marine invertebrates. The results from 71 stations show that much can still be done by the 28 nations operating the 82 research stations in Antarctica. The technology exists for effective waste water treatment in the challenging Antarctic conditions. The use of efficient technology at all permanent Antarctic research stations would greatly reduce the human impact on the pristine Antarctic environment. In order to protect the Antarctic environment from infectious agents introduced by humans, consideration should also be given to preventing the release of untreated waste water and grey water from the smaller summer stations.
Keywords: Dronning Maud Land; avfallshåndtering; forskningsstasjoner; menneskelig påvirkning; miljøvern; økologi

Atmospheric monitoring at the Norwegian Antarctic station Troll: measurement programme and first results - Hansen, Georg; Aspmo, Katrine; Berg, Torunn; Edvardsen, Kåre; Fiebig, Markus; Kallenborn, Roland; Krognes, Terje; Lunder, Chris; Stebel, Kersten; Schmidbauer, Norbert; Solberg, Sverre; Yttri, Karl Espen (Polar Research, 2009)
The Troll Atmospheric Station in Antarctica (72°01'S, 2°32'E, 1309 m a.s.l.) was established and put into operation in early 2007. The main foci of the measurement programme are pollution and aerosols in the transition zone between the coastal zone and the inland ice plateau, complementing existing observation programmes along the Antarctic coast and on the Antarctic Plateau. After one year of operation, the monitoring programme is fully operative, and a comprehensive set of data is being analysed. As far as comparable data are available, there is satisfactory agreement between previous and new data. Both aerosol data and measurements of pollution indicate the episodic influence of coastal air masses throughout the year. Background values of medium long-lived pollutants such as CO, O3 and Hg are up to 50% lower than at corresponding Arctic sites (depending on the season), but are still significant. Total ozone and UV doses manifest the recurring Antarctic stratospheric ozone hole, which was moderately severe, but very persistent in 2007. Specific episodes of elevated aerosol concentration and mercury activation are currently under detailed investigation, and will be published separately.
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; forurensning; meteorologi; målinger; ozonlaget

The water column as an attenuating factor of the UVR effects on bacteria from a coastal Antarctic marine environment - Hernández, Edgardo A; Ferreyra, Gustavo A; Ruberto, Lucas A M; Mac Cormack, Walter P (Polar Research, 2009)
The effect of UVR on the viability of the culturable bacterial community fraction (CBC), and two of their isolated components (Arthrobacter-UVvi and Bizionia-UVps), was studied in the top few metres of the water column at Potter Cove, King George Island, Antarctica. Quartz flasks containing CBC from surface waters were exposed to solar radiation at depths of 0, 1 and 3 m. Similar experiments using UVps and UVvi isolates were performed. In some experiments interferential filters were used to discriminate photosynthetic active radiation (PAR), UV-A and UV-B. CBC from depths of 0, 10 and 30 m were also exposed to surface solar radiation. The deleterious effect of UVR was observed at the surface and at a depth of 1 m, but not at a depth of 3 m. Studies with interferential filters showed low bacterial viability values at depths of 0 and 1 m under both UVR treatments. However, under low radiation doses the effect attributed to UV-B was higher than that caused by UV-A. The surface CBC was more resistant to UVR compared with CBC from a depth of 30 m. The results showed that CBC inhabiting waters above the pycnocline (located at a depth of 5–10 m) are more efficiently adapted to UVR than are those from below the pycnocline. The impact of UVR on the marine bacterioplankton studied was only detected in the first metre of the stratified water column of Potter Cove, which has high levels of suspended particulate matter. These results support the evidence for a significant UVR-attenuating effect in the water column of this coastal Antarctic water.
Keywords: Sørishavet; UV-stråling; bakterier; marin biologi; plankton; statistisk analyse; ultrafiolett stråling; vannsøyle

Vill etter krill : på ekspedisjon med G.O. SARS til Sørishavet - Iversen, Svein A (Red.); Myklevoll, Sigmund (Red.); Mæstad, Kjartan (Red.); Nøttestad, Leif (Red.) (Havforskningsinstituttet, 2009)
Keywords: Sørishavet; ekspedisjoner; euphausiacea; forskning; krill; marin biologi; marine økosystemer; plankton; raudåte

Vill etter krill : på ekspedisjon med G.O. SARS til Sørishavet - Iversen, Svein A; Myklevoll, Sigmund; Mæstad, Kjartan; Nøttestad, Leif; Alvarez, Jaime (Havforskningsinstituttet, 2009)
Keywords: Sørishavet; ekspedisjoner; krill; marin biologi; raudåte; økosystemer

A review of two decades (1986 2008) of geochronological work in Heimefrontfjella, and geotectonic interpretation of western Dronning Maud Land, East Antarctica - Jacobs, Joachim (Polarforschung, 2009)
During two decades (1986 - 2008) of geochronological work in Heimefrontfjella, nearly 130 geochronological ages were produced using a wide range of geochronological techniques. The ages fall into four broad age groups from Archaean to Cenozoic times, revealing a long and complex geological history. In general, Heimefrontfjella consists of Mesoproterozoic high grade basement related to the ∼1100 Ma Maud Belt. This basement is overlain by Permo-Carboniferous sedimentary rocks and Jurassic lavas. Archaean and Palaeoproterozoic detrital zircon ages are recorded from meta-sedimentary rocks probably characterizing the foreland of the Maud Belt. The protolith and metamorphic ages of the Mesoproterozoic Maud Belt fall into two groups. An older age group from ∼1200-1100 Ma is related to back-arc and island arc volcanism. High-grade metamorphism in the Maud Belt is dated between 1090-1060 Ma and is thought to reflect continent-continent collision, possibly related to the formation of Rodinia. Regional cooling to below 500-300 °C at ∼1010-960 Ma in part of the mountain range might indicate rifting of Rodinia. The eastern part of the mountain range is overprinted by the ∼600-500 Ma East African-Antarctic Orogen. The orogenic front of this major mobile belt is exposed in the study area as the Heimefront Shear Zone. East of this major lineament all Ar-Ar, K-Ar and Rb-Sr mineral ages are reset to ∼500 Ma. Initial Gondwana rifting affected the area at c. 180 Ma, when the Bouvet/Karroo mantle plume caused dynamic uplift of the area, followed by burial underneath up to 2 km of Jurassic lava. This led to tempering of the basement up to about 100 °C, as indicated by apatite fission track data. The lava pile underwent erosion in Cretaceous time, when renewed rifting affected the region. Latest tectonic movements might be related to Cenozoic ice loading related to the built up of the Antarctic ice sheet.
Keywords: Dronning Maud Land; ekspedisjoner; geokronologi; geologi; tektonikk

Geological map of Heimefrontfjella, Dronning Maud Land, Antarctica (Scale 1:250,000) - Jacobs, Joachim; Bauer, Wilfried; Kreutzer, Stefan; Patzelt, Gernot; Schmidt, Rainer; Schulze, Peter; Siegesmund, Siegfried; Spaeth, Gerhard; Thomas, Robert J; Weber, Klaus; Zarske, Gerd (PANGAEA, 2009)
The geological overview map was compiled from 15 geological maps (1 : 25,000) and is based on Jacobs et al. 1996. The topographic basemaps were adapted from unpublished 1:250,000 provisional topographic maps, Institut f. Angewandte Geodäsie, Frankfurt, 1983. Part of the contour lines are from Radarsat (Liu et al. 2001).
Keywords: Dronning Maud Land; geologi; kart; topografi

Cold Recall : Reflections of a Polar Explorer - Kløver, Geir O (Red.) (The Fram Museum, 2009)
Keywords: Antarktis; Roald Amundsen; Sydpolekspedisjon; oppdagelsesreiser

Kvalfangst i Sørishavet - Knarvik, Olaf (Kjelda, 2009)
Keywords: Sørishavet; fotografi; hvalfangst

Ice-ocean processes over the continental shelf of the southern Weddell Sea, Antarctica: A review - Nicholls, Keith W.; Østerhus, Svein; Makinson, Keith; Gammelsrød, Tor; Fahrbach, Eberhard (Reviews of Geophysics, 2009)
Interactions between the Southern Ocean and the Weddell Sea ice shelves are important both to the Antarctic Ice Sheet and to the production of globally significant water masses. Here we review the interaction between the Filchner-Ronne Ice Shelf and the shelf sea in which it floats. The continental shelf processes leading to the production of Weddell Sea deep and bottom waters from the original off-shelf source waters are discussed, and a new view is offered of the initial production of High-Salinity Shelf Water. Data from ship-based measurements at the ice front, from glaciological methods, and from measurements made within the sub–ice shelf cavity itself are used to describe the pattern of flows beneath the ice shelf. We also consider the variability observed within the cavity from tidal to interannual time scales and finish with a discussion of future research priorities in the region.
Keywords: AABW; Antarktis; Sørishavet; Weddellhavet; glasiologi; innlandsis; isfront; isshelf; oseanografi; vannmasser

Evolution of first-year and second-year snow properties on sea ice in the Weddell Sea during spring-summer transition - Nicolaus, Marcel; Haas, Christian; Willmes, Sascha (Journal of Geophysical Research: Atmospheres, 2009)
Observations of snow properties, superimposed ice, and atmospheric heat fluxes have been performed on first-year and second-year sea ice in the western Weddell Sea, Antarctica. Snow in this region is particular as it does usually survive summer ablation. Measurements were performed during Ice Station Polarstern (ISPOL), a 5-week drift station of the German icebreaker RV Polarstern. Net heat flux to the snowpack was 8 W m−2, causing only 0.1 to 0.2 m of thinning of both snow cover types, thinner first-year and thicker second-year snow. Snow thinning was dominated by compaction and evaporation, whereas melt was of minor importance and occurred only internally at or close to the surface. Characteristic differences between snow on first-year and second-year ice were found in snow thickness, temperature, and stratigraphy. Snow on second-year ice was thicker, colder, denser, and more layered than on first-year ice. Metamorphism and ablation, and thus mass balance, were similar between both regimes, because they depend more on surface heat fluxes and less on underground properties. Ice freeboard was mostly negative, but flooding occurred mainly on first-year ice. Snow and ice interface temperature did not reach the melting point during the observation period. Nevertheless, formation of discontinuous superimposed ice was observed. Color tracer experiments suggest considerable meltwater percolation within the snow, despite below-melting temperatures of lower layers. Strong meridional gradients of snow and sea-ice properties were found in this region. They suggest similar gradients in atmospheric and oceanographic conditions and implicate their importance for melt processes and the location of the summer ice edge.
Keywords: Sørishavet; Weddellhavet; atmosfæren; havis; klimatologi; meteorologi; målinger; oseanografi; sjøis; snø; økosystemer

Movements and dive behaviour of two leopard seals (Hydrurga leptonyx) off Queen Maud Land, Antarctica - Nordøy, Erling S; Blix, Arnoldus Schytte (Polar Biology, 2009)
Keywords: Sørishavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr

Observations on the relationship between the Antarctic coastal diatoms Thalassiosira antarctica Comber and Porosira glacialis (Grunow) Jørgensen and sea ice concentrations during the late Quaternary - Pike, Jennifer; Crosta, Xavier; Maddison, Eleanor J.; Stickley, Catherine E.; Denis, Delphine; Barbara, Loïc; Renssen, Hans (Marine Micropaleontology, 2009)
The available ecological and palaeoecological information for two sea ice-related marine diatoms (Bacillariophyceae), Thalassiosira antarctica Comber and Porosira glacialis (Grunow) Jørgensen, suggests that these two species have similar sea surface temperature (SST), sea surface salinity (SSS) and sea ice proximity preferences. From phytoplankton observations, both are described as summer or autumn bloom species, commonly found in low SST waters associated with sea ice, although rarely within the ice. Both species form resting spores (RS) as irradiance decreases, SST falls and SSS increases in response to freezing ice in autumn. Recent work analysing late Quaternary seasonally laminated diatom ooze from coastal Antarctic sites has revealed that sub-laminae dominated either by T. antarctica RS, or by P. glacialis RS, are nearly always deposited as the last sediment increment of the year, interpreted as representing autumn flux. In this study, we focus on sites from the East Antarctic margin and show that there is a spatial and temporal separation in whether T. antarctica RS or P. glacialis RS form the autumnal sub-laminae. For instance, in deglacial sediments from the Mertz Ninnis Trough (George V Coast) P. glacialis RS form the sub-laminae whereas in similar age sediments from Iceberg Alley (Mac.Robertson Shelf) T. antarctica RS dominate the autumn sub-lamina. In the Dumont d'Urville Trough (Adélie Land), mid-Holocene (Hypsithermal warm period) autumnal sub-laminae are dominated by T. antarctica RS whereas late Holocene (Neoglacial cool period) sub-laminae are dominated by P. glacialis RS. These observations from late Quaternary seasonally laminated sediments would appear to indicate that P. glacialis prefers slightly cooler ocean–climate conditions than T. antarctica. We test this relationship against two down-core Holocene quantitative diatom abundance records from Dumont d'Urville Trough and Svenner Channel (Princess Elizabeth Land) and compare the results with SST and sea ice concentration results of an Antarctic and Southern Ocean Holocene climate simulation that used a coupled atmosphere–sea ice–vegation model forced with orbital parameters and greenhouse gas concentrations. We find that abundance of P. glacialis RS is favoured by higher winter and spring sea ice concentrations and that a climatically-sensitive threshold exists between the abundance of P. glacialis RS and T. antarctica RS in the sediments. An increase to >0.1 for the ratio of P. glacialis RS:T. antarctica RS indicates a change to increased winter sea ice concentration (to >80% concentration), cooler spring seasons with increased sea ice, slightly warmer autumn seasons with less sea ice and a change from ~7.5months annual sea ice cover at a site to much greater than 7.5months. In the East Antarctic sediment record, an increase in the ratio from <0.1 to above 0.1 occurs at the transition from the warmer Hypsithermal climate into the cooler Neoglacial climate (~4cal kyr) indicating that the ratio between these two diatoms has the potential to be used as a semi-quantitative climate proxy.
Keywords: Sørishavet; Weddellhavet; diatomeer; havis; marin biologi; mikropaleontologi; paleontologi; paleoøkologi; sjøis

Antarctic ascidians: an isolated and homogeneous fauna - Primo, Carmen; Vázquez, Elsa (Polar Research, 2009)
Several biogeographical studies have already been performed on the ascidians of the Antarctic region. However, new data obtained in the last few years have led us to a revision of the biogeography of this fauna. To examine the biogeographical structure of the Antarctic region, we divided it into 10 sectors, depending on the principal geographical features, and then applied cluster analysis and a multi-dimensional scaling ordination to a presence/absence matrix of species for each biogeographical area. Our study shows that Antarctic ascidians are a very homogeneous fauna, with a high level of endemism in the whole region (25–51% of Antarctic endemic species per sector), but with a low percentage of sector endemism (only up to 10%). This probably results from isolation arising from the Antarctic Convergence, and the vast geographical distances from adjacent regions, as well as from the relative constancy of the hydrographical conditions and the dispersal of organisms through circumpolar currents. In fact, cosmopolitan species represented only 0–7% of the total ascidian fauna in all sectors. Only the Bellingshausen Sea (low sample size), Bouvetøya (young and isolated, with an impoverished ascidian fauna) and the South Sandwich Islands (also young and isolated) are relatively separated. The insular sectors were more closely related to the South America and sub- Antarctic regions than the continental ones, showing a latitudinal gradient.
Keywords: Sørishavet; biogeografi; fauna; sekkdyr; zoogeografi

Impacts of the Oceans on Climate Change - Reid, Philip C; Fischer, Astrid C; Lewis-Brown, Emily; Meredith, Michael P; Sparrow, Mike; Andersson, Andreas J; Antia, Avan; Bates, Nicholas R; Bathmann, Ulrich; Beaugrand, Gregory; Brix, Holger; Dye, Stephen; et al. (Advances in Marine Biology, 2009)
The oceans play a key role in climate regulation especially in part buffering (neutralising) the effects of increasing levels of greenhouse gases in the atmosphere and rising global temperatures. This chapter examines how the regulatory processes performed by the oceans alter as a response to climate change and assesses the extent to which positive feedbacks from the ocean may exacerbate climate change. There is clear evidence for rapid change in the oceans. As the main heat store for the world there has been an accelerating change in sea temperatures over the last few decades, which has contributed to rising sea‐level. The oceans are also the main store of carbon dioxide (CO2), and are estimated to have taken up ∼40% of anthropogenic-sourced CO2 from the atmosphere since the beginning of the industrial revolution. A proportion of the carbon uptake is exported via the four ocean ‘carbon pumps’ (Solubility, Biological, Continental Shelf and Carbonate Counter) to the deep ocean reservoir. Increases in sea temperature and changing planktonic systems and ocean currents may lead to a reduction in the uptake of CO2 by the ocean; some evidence suggests a suppression of parts of the marine carbon sink is already underway. While the oceans have buffered climate change through the uptake of CO2 produced by fossil fuel burning this has already had an impact on ocean chemistry through ocean acidification and will continue to do so. Feedbacks to climate change from acidification may result from expected impacts on marine organisms (especially corals and calcareous plankton), ecosystems and biogeochemical cycles. The polar regions of the world are showing the most rapid responses to climate change. As a result of a strong ice–ocean influence, small changes in temperature, salinity and ice cover may trigger large and sudden changes in regional climate with potential downstream feedbacks to the climate of the rest of the world. A warming Arctic Ocean may lead to further releases of the potent greenhouse gas methane from hydrates and permafrost. The Southern Ocean plays a critical role in driving, modifying and regulating global climate change via the carbon cycle and through its impact on adjacent Antarctica. The Antarctic Peninsula has shown some of the most rapid rises in atmospheric and oceanic temperature in the world, with an associated retreat of the majority of glaciers. Parts of the West Antarctic ice sheet are deflating rapidly, very likely due to a change in the flux of oceanic heat to the undersides of the floating ice shelves. The final section on modelling feedbacks from the ocean to climate change identifies limitations and priorities for model development and associated observations. Considering the importance of the oceans to climate change and our limited understanding of climate-related ocean processes, our ability to measure the changes that are taking place are conspicuously inadequate. The chapter highlights the need for a comprehensive, adequately funded and globally extensive ocean observing system to be implemented and sustained as a high priority. Unless feedbacks from the oceans to climate change are adequately included in climate change models, it is possible that the mitigation actions needed to stabilise CO2 and limit temperature rise over the next century will be underestimated.
Keywords: Sørishavet; global oppvarming; havnivåstigning; klimaendringer; klimatologi

Large-scale force budget: identification of interest areas and assessment of a data set for the large drainage basin of Jutulstraumen, East Antarctica - Rolstad, Cecilie (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 2009)
A large-scale force budget is a relatively simple but useful tool for initial investigation of ice dynamics; however, it requires an extensive data set. Identification of key measurement areas and assessment of the spatial variability of the required measurement accuracies is advantageous prior to measuring such large drainage basins. Identification of areas and assessment of data requires several steps and in the paper velocities and surface topography are modelled numerically for Jutulstraumen drainage basin, representing ~1% of the Antarctic ice sheet (124,000 km2). A preliminary large-scale force budget is calculated from the modelled results, and key areas are identified. Finally, the required measurement accuracies yielding 10% uncertainty of the estimated stresses are calculated through error propagation of the force budget equations. Based on the results it is recommended to prioritize more accurate measurements for determining the driving stresses for the entire basin, and the longitudinal stresses in the funnel area of Jutulstraumen. The required measurement accuracy varies strongly over the basin, limiting the effective use of remote sensed data for deriving stresses. Radar altimetry surface elevation data can be used on the lower half of the plateau, and InSAR velocity data on the lower parts of the plateau and down-glacier.
Keywords: Dronning Maud Land; glasiologi; modellering

Asymmetries in the moisture origin of Antarctic precipitation - Sodemann, Harald; Stohl, Andreas (Geophysical Research Letters, 2009)
The seasonality of moisture sources for precipitation in Antarctica is studied with a Lagrangian moisture source diagnostic. Moisture origin for precipitation in Antarctica has strongly asymmetric properties, which are related to the Antarctic topography, seasonal sea ice coverage, and the land/ocean contrasts in the mid-latitudes of the southern hemisphere. The highest altitudes of the East Antarctic ice shield, where major ice cores have been drilled, have mean source latitudes of 45–40°S year-round. This finding contrasts to results from previous Lagrangian studies which detected a more southerly moisture origin due to too short trajectories. Now, results from Lagrangian moisture source diagnostics are consistent with findings from general circulation models with tagged tracers. Thus, both approaches can serve as a common benchmark for the interpretation of moisture source indicators based on stable isotopes, such as deuterium excess, in Antarctic ice cores.
Keywords: Antarktis; klimatologi; meteorologi; nedbør

Variability and predictability of Antarctic krill swarm structure - Tarling, Geraint A.; Klevjer, Thor; Fielding, Sophie; Watkins, Jon; Atkinson, Angus; Murphy, Eugene; Korb, Rebecca; Whitehouse, Mick; Leaper, Russell (Deep Sea Research Part I: Oceanographic Research Papers, 2009)
Swarming is a fundamental part of the life of Euphausia superba, yet we still know very little about what drives the considerable variability in swarm shape, size and biomass. We examined swarms across the Scotia Sea in January and February 2003 using a Simrad EK60 (38 and 120kHz) echosounder, concurrent with net sampling. The acoustic data were analysed through applying a swarm-identification algorithm and then filtering out all non-krill targets. The area, length, height, depth, packing-concentration and inter-swarm distance of 4525 swarms was derived by this method. Hierarchical clustering revealed 2 principal swarm types, which differed in both their dimensions and packing-concentrations. Type 1 swarms were generally small (<50m long) and were not very tightly packed (<10ind.m−3), whereas type 2 swarms were an order of magnitude larger and had packing concentrations up to 10 times greater. Further sub-divisions of these types identified small and standard swarms within the type 1 group and large and superswarms within the type 2 group. A minor group (swarm type 3) was also found, containing swarms that were isolated (>100km away from the next swarm). The distribution of swarm types over the survey grid was examined with respect to a number of potential explanatory variables describing both the environment and the internal-state of krill (namely maturity, body length, body condition). Most variables were spatially averaged over scales of ∼100km and so mainly had a mesoscale perspective. The exception was the level of light (photosynthetically active radiation (PAR)) for which measurements were specific to each swarm. A binary logistic model was constructed from four variables found to have significant explanatory power (P<0.05): surface fluorescence, PAR, krill maturity and krill body length. Larger (type 2) swarms were more commonly found during nighttime or when it was overcast during the day, when surface fluorescence was low, and when the krill were small and immature. A strong pattern of diel vertical migration was not observed although the larger and denser swarms tended to occur more often at night than during the day. The vast majority of krill were contained within a minor fraction of the total number of swarms. These krill-rich swarms were more common in areas dominated by small and immature krill. We propose that, at the mesoscale level, the structure of swarms switches from being predominantly large and tightly packed to smaller and more diffuse as krill grow and mature. This pattern is further modulated according to feeding conditions and then level of light.
Keywords: Scotiahavet; Sørishavet; ekkolodd; krill; marin biologi; marine økosystemer; plankton

Contrasting climate change in the two polar regions - Turner, John; Overland, Jim (Polar Research, 2009)
The two polar regions have experienced remarkably different climatic changes in recent decades. The Arctic has seen a marked reduction in sea-ice extent throughout the year, with a peak during the autumn. A new record minimum extent occurred in 2007, which was 40% below the long-term climatological mean. In contrast, the extent of Antarctic sea ice has increased, with the greatest growth being in the autumn. There has been a large-scale warming across much of the Arctic, with a resultant loss of permafrost and a reduction in snow cover. The bulk of the Antarctic has experienced little change in surface temperature over the last 50 years, although a slight cooling has been evident around the coast of East Antarctica since about 1980, and recent research has pointed to a warming across West Antarctica. The exception is the Antarctic Peninsula, where there has been a winter (summer) season warming on the western (eastern) side. Many of the different changes observed between the two polar regions can be attributed to topographic factors and land/sea distribution. The location of the Arctic Ocean at high latitude, with the consequently high level of solar radiation received in summer, allows the icealbedo feedback mechanism to operate effectively. The Antarctic ozone hole has had a profound effect on the circulations of the high latitude ocean and atmosphere, isolating the continent and increasing the westerly winds over the Southern Ocean, especially during the summer and winter.
Keywords: Antarktis; Sørishavet; havis; klimaendringer; klimatologi; ozonhull; ozonlaget; polarområdene; sjøis

Pleomorphism in the Antarctic flagellate Pyramimonas gelidicola (Prasinophyceae, Chlorophyta) - van den Hoff, John; Ferris, John M (Polar Research, 2009)
Species of the genus Pyramimonas (Prasinophyceae) are a common, widespread, but minor component of the Antarctic marine phytoplankton. They are often associated with the seasonal sea-ice environment. Pyramimonas gelidicola (McFadden, Moestrup & Wetherbee, 1982) was isolated from the water column of a saline Antarctic lake, and observations on the organism’s life history as it grew in unialgal cultures were made. The alga proved to be pleomorphic: capable of producing several morphologically distinct life stages. We recorded motile single-celled quadriflagellates that formed two statistically distinct size classes, a rare uniflagellate cell-type, and aggregations of quadriflagellate cells, multilobed forms and an encystment stage. Multilobed forms and cell aggregations, never before observed in an Antarctic Pyramimonas species, are presumed to be growth medium-induced morphotypes. Multilobed forms contained an equal number of nuclei and lobes, suggesting that they are the product of asexual reproduction. Some of the morphotypes we report here may never be observed under natural field conditions, but the potential for this alga to alternate between morphotypes is clearly demonstrated.
Keywords: Sørishavet; alger; fytoplankton; marin biologi

Two decades of geological mapping and research in Heimefrontfjella, Dronning Maud Land, Antarctica - Weber, Klaus; Jacobs, Joachim (Polarforschung, 2009)
Heimefrontfjella is a strongly segmented NE–SW trending mountain range some 130 km long with a maximum width of about 30 km. The range takes the form of a prominent escarpment, which rises more than 1000 m above the ice plains to the northwest. The maximum elevation reaches 2700 m above sea level. Since its discovery during the German Antarctic Expedition 1938/39, very few scientists had visited Heimefrontfjella by 1985. During the mid 1960s two British geologists had visited the Heimefrontfjella and provided a geological overview of the area. Thereafter, detailed geological investigations became possible with the establishment of the Georg von Neumayer Station on the Ekström ice shelf in 1981, situated some 450 km north of Heimefrontfjella. Since then, the Georg von Neumayer Station has provided a logistical base for multidisciplinary research programs within the Atlantic sector of East Antarctica.
Keywords: Dronning Maud Land; ekspedisjoner; geologi; kartlegging

Satellite microwave observations of the interannual variability of snowmelt on sea ice in the Southern Ocean - Willmes, Sascha; Haas, Christian; Nicolaus, Marcel; Bareiss, Jörg (Journal of Geophysical Research: Oceans, 2009)
Snowmelt processes on Antarctic sea ice are examined. We present a simple snowmelt indicator based on diurnal brightness temperature variations from microwave satellite data. The method is validated through extensive field data from the western Weddell Sea and lends itself to the investigation of interannual and spatial variations of the typical snowmelt on Antarctic sea ice. We use in-situ measurements of physical snow properties to show that despite the absence of strong melting, the summer period is distinct from all other seasons with enhanced diurnal variations of snow wetness. A microwave emission model reveals that repeated thawing and refreezing cause the typical microwave emissivity signatures that are found on perennial Antarctic sea ice during summer. The proposed melt indicator accounts for the characteristic phenomenological stages of snowmelt in the Southern Ocean and detects the onset of diurnal snow wetting. An algorithm is presented to map large-scale snowmelt onset based on satellite data from the period between 1988 and 2006. The results indicate strong meridional gradients of snowmelt onset with the Weddell, Amundsen, and Ross Seas showing earliest (beginning of October) and most frequent snowmelt. Moreover, a distinct interannual variability of melt onset dates and large areas of first-year ice where no diurnal freeze thawing occurs at the surface are determined.
Keywords: Amundsenhavet; Rosshavet; Sørishavet; Weddellhavet; fjernmåling; havis; miljøsatellitter; oseanografi; sjøis; snøsmelting

Metabolism and biomass vertical distribution of zooplankton in the Bransfield Strait during the austral summer of 2000 - Yebra, Lidia; Hernández-León, Santiago; Almeida, Carlos; Bécognée, Pierrick (Polar Research, 2009)
The vertical distribution (0–550 m) of zooplankton biomass, and indices of respiration (electron transfer system [ETS]) and structural growth (aminoacyltRNA synthetases activity [AARS]), were studied in waters off the Antarctic Peninsula during the austral summer of 2000. The dominant species were the copepod Metridia gerlachei and the euphausiid Euphausia superba. We observed a vertical krill/copepod substitution in the water column. The zooplankton biomass in the layer at a depth of 200–500 m was of the same magnitude as the biomass in the layer at a depth of 0–200 m, indicating that biomass in the mesopelagic zone is an important fraction of the total zooplankton in Antarctic waters. The metabolic rates of the zooplankton community were sustained by less than 0.5% of the primary production in the area, suggesting that microplankton or small copepods are the main food source. Neither food availability nor predation seemed to control mesozooplankton biomass. The wide time lag between the abundance peak of the dominant copepod (M. gerlachei) and the phytoplankton bloom is suggested to be the main explanation for the low summer zooplankton biomass observed in these waters.
Keywords: Sørishavet; biomasse; fytoplankton; hydrologi; krill; metabolisme; oseanografi; zooplankton

Sedimentological, geochemical and palaeontological evidence for a neoglacial cold event during the late Holocene in the continental shelf of the northern South Shetland Islands, West Antarctica - Yoo, Kyu-Cheul; Yoon, Ho Il; Kim, Jin-Kyung; Khim, Boo-Keun (Polar Research, 2009)
Two sediment cores obtained from the continental shelf of the northern South Shetland Islands, West Antarctica, consist of: an upper unit of silty mud, bioturbated by a sluggish current, and a lower unit of well-sorted, laminated silty mud, attributed to an intensified Polar Slope Current. Geochemical and accelerator mass spectrometry 14C analyses yielded evidence for a late Holocene increase in sea-ice extent and a decrease in phytoplankton productivity, inferred from a reduction in the total organic carbon content and higher C : N ratios, at approximately 330 years B.P., corresponding to the Little Ice Age. Prior to this, the shelf experienced warmer marine conditions, with greater phytoplankton productivity, inferred from a higher organic carbon content and C : N ratios in the lower unit. The reduced abundance of Weddell Sea ice-edge bloom species (Chaetoceros resting spores, Fragilariopsis curta and Fragilariopsis cylindrus) and stratified cold-water species (Rhizosolenia antennata) in the upper unit was largely caused by the colder climate. During the cold period, the glacial restriction between the Weddell Sea and the shelf of the northern South Shetland Islands apparently hindered the influx of ice-edge bloom species from the Weddell Sea into the core site. The relative increases in the abundance of Actinocyclus actinochilus and Navicula glaciei, indigenous to the coastal zone of the South Shetland Islands, probably reflects a reduction in the dilution of native species, resulting from the diminished influx of the ice-edge species from the Weddell Sea. We also document the recent reduction of sea-ice cover in the study area in response to recent warming along the Antarctic Peninsula.
Keywords: Antarktis; Den lille istid; Vestantarktis; Weddellhavet; diatomeer; fytoplankton; geokjemi; havis; klimaendringer; klimatologi; kontinentalsokkel; marin biologi; mikropaleontologi; oseanografi; sedimenter; sedimentologi; sjøis

Self-scattering of a powerful HF radio wave on stimulated ionospheric turbulence - Zalizovski, Andriy; Kashcheyev, S B; Yampolski, Y M; Galushko, V G; Belyey, Vasyl; Isham, B; Rietveld, M T; La Hoz, C; Brekke, A; Blagoveshchenskaya, N F; Kornienko, V A (Radio Science, 2009)
An analysis is presented of high-frequency (HF) signals from the European Incoherent Scatter HF ionospheric modification transmitter received during 26–30 October 2002 at three sites, two in Europe and one in Antarctica. Two components with different characteristics (“mirror-reflected” and “scattered”) were observed in the signal spectra. The mirror-reflected component can be associated with radiation through the side lobes of the transmitting antenna thus bypassing the modified volume on its way to the receiving sites. In contrast, the scattered component was radiated through the main antenna beam and then scattered by pump-induced ionospheric irregularities above the heater. As a result, variations in the scattered component signal intensity and Doppler frequency shifts (DFS) recorded at the greatly separated sites showed a high level of correlation. It is shown that the Doppler frequency variations can be associated with variations in the plasma density and/or physical motion velocities of stimulated inhomogeneities within the volume common to all propagation paths. Analysis of Doppler frequency shifts at greatly separated sites would allow identifying the mechanism responsible for the self-scattering effect. In the case of DFSs due to motion of the pump-induced scatterers it would be also possible to reconstruct the full velocity vector of the inhomogeneities.
Keywords: Antarktis; astronomi; fysikk; ionosfæren; polarområdene